2020
DOI: 10.1097/hs9.0000000000000509
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy for Primary Immunodeficiency

Abstract: Over the past 3 decades, there has been significant progress in refining gene therapy technologies and procedures. Transduction of hematopoietic stem cells ex vivo using lentiviral vectors can now create a highly effective therapeutic product, capable of reconstituting many different immune system dysfunctions when reinfused into patients. Here, we review the key developments in the gene therapy landscape for primary immune deficiency, from an experimental therapy where clinical efficacy was marred by adverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 174 publications
0
15
0
3
Order By: Relevance
“…Later trials discontinued enzyme replacement after gene correction and used non-myeloablative conditioning to improve engraftment. Strimvelis, the first ex vivo gene therapy product to receive regulatory approval in the world, was approved in Europe in 2016, based on data from 18 patients with ADA-SCID who were treated from 2000 to 2011 with a median follow-up of 7 years, showing 100% survival and evidence of long-term gene correction in T cells and maintenance of immune reconstitution [ 35 , 37 42 ]. Until recently, there had been no reports of insertional oncogenesis or leukemic proliferation observed in greater than 40 ADA patients treated with gamma-retroviral vector gene therapy, but it has been recently reported that a patient treated with Strimvelis for ADA-SCID was diagnosed with T cell leukemia and the cause is under investigation.…”
Section: Stem Cell Transplantation and Gene Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…Later trials discontinued enzyme replacement after gene correction and used non-myeloablative conditioning to improve engraftment. Strimvelis, the first ex vivo gene therapy product to receive regulatory approval in the world, was approved in Europe in 2016, based on data from 18 patients with ADA-SCID who were treated from 2000 to 2011 with a median follow-up of 7 years, showing 100% survival and evidence of long-term gene correction in T cells and maintenance of immune reconstitution [ 35 , 37 42 ]. Until recently, there had been no reports of insertional oncogenesis or leukemic proliferation observed in greater than 40 ADA patients treated with gamma-retroviral vector gene therapy, but it has been recently reported that a patient treated with Strimvelis for ADA-SCID was diagnosed with T cell leukemia and the cause is under investigation.…”
Section: Stem Cell Transplantation and Gene Therapymentioning
confidence: 99%
“…Until recently, there had been no reports of insertional oncogenesis or leukemic proliferation observed in greater than 40 ADA patients treated with gamma-retroviral vector gene therapy, but it has been recently reported that a patient treated with Strimvelis for ADA-SCID was diagnosed with T cell leukemia and the cause is under investigation. [ 35 ] The most recent trials, which are ongoing in the UK and US, are using a safer self-inactivating lentiviral vector with codon optimized cDNA for adenosine deaminase under control of an elongation factor (elongation factor 1α) promoter with continuation of ERT for one month after gene therapy. For up to 3 years of follow-up, the 30 treated patients have shown excellent efficacy and no associated genotoxicity.…”
Section: Stem Cell Transplantation and Gene Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, allogeneic hematopoietic stem cell transplantation (HSCT) remains the treatment of choice but the genetic subtype greatly impacts long-term survival and immune reconstitution (16). Therefore, for some SCID genetic defects, gene therapy studies using autologous stem cells seem to be promising as an alternative approach to cure disease as illustrated for ADA-, IL2RG-and ARTEMIS-SCID (17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%